Erythrocytosis in patients taking long-term hemodialysis: A case series (Indian Journal of Case Reports, 2025)
Anemia is one of the common findings and complications in patients with end-stage kidney disease (ESRD). Most patients need to take the therapies to control target hemoglobin level and these treatments can add to the high cost and adverse events in these patients. In our hemodialysis center, regular monitoring of hemoglobin was done for all regular hemodialysis patients and we found that two patients who have different etiologies of ESRD had high hemoglobin levels without the help of erythropoietin stimulating agents and blood transfusion. They had the duration of hemodialysis for more than 10 years and they were found to have acquired cystic kidney disease at the time of assessing the etiologies of erythrocytosis. There are few case reports and research about erythrocytosis due to acquired cystic kidney disease. Acquired cystic kidney disease is frequently found in patients with longer duration of dialysis and erythrocytosis is one of the beneficial consequences for chronic kidney disease patients. It can avoid the high cost of erythropoietin-stimulating agent and iron therapy, and their adverse events. Phlebotomy is an easy way to maintain the level of hemoglobin in such patients.